Endodontic treatment in HIV patients: An integrative review (Research, Society and Development, 2023)
Endodontic treatment in patients with HIV requires special attention, since they have a syndrome (AIDS) with an immunosuppressive effect, increasing the risk of secondary infections and complications. The present study aims to provide information to dental professionals, through an integrative review, so that they are prepared to deal with these situations, with the use of preventive measures for biosafety, such as the use of personal protective equipment, in addition to adopting a care protocol that includes the assessment of the patient's clinical conditions and the use of conservative measures. It is essential to maintain the necessary care, ensuring the effectiveness and safety of the procedure. Endodontic treatment protocols for different patient conditions and pharmacological protocols are also presented. These protocols also seek to present ways to guarantee the patient's health, the professional's safety, treatment effectiveness and the patient's moral integrity. The results of the research reported that, even with Acquired Immune Deficiency Syndrome, the endodontic treatment of an HIV patient is not so different from that of a normosystemic patient, the response during treatment and recovery is very similar, but all measures must be reinforced biosafety measures to avoid cross-infection. It was concluded that the presence of knowledge during endodontic treatment is vital for the success of the treatment, seeking the study of endodontic protocols, the study of special patients and their needs and pharmacological knowledge, in addition to ethical knowledge and always seeking empathy towards the patient.